City of Marvel and Transformation : Changan and Narratives of Experience in Tang Dynasty China - Feng, Linda Rui, 1975- (Book collections on Project MUSE., 2016)
During the Tang dynasty, the imperial capital of Chang'an (present-day Xi'an) was unrivaled in its monumental scale. City of Marvel and Transformation brings this cityscape to life together with the mindscape of its sojourner-writers. By analyzing narratives of experience with a distinctive metropolitan consciousness, it retrieves lost connections between senses of the self and a sense of place.